Animal-Friendly Affinity Reagents: Replacing the Needless in the Haystack. Issue 12 (December 2016) - Gray, A.C.; Sidhu, S.S.; Chandrasekera, P.C.; Hendriksen, C.F.M.; Borrebaeck, C.A.K.
Abstract : The multibillion-dollar global antibody industry produces an indispensable resource but that is generated using millions of animals. Despite the irrefutable maturation and availability of animal-friendly affinity reagents (AFAs) employing naïve B lymphocyte or synthetic recombinant technologies expressed by phage display, animal immunisation is still authorised for antibody production. Remarkably, replacement opportunities have been overlooked, despite the enormous potential reduction in animal use. Directive 2010/63/EU requires that animals are not used where alternatives exist. To ensure its implementation, we have engaged in discussions with the EU Reference Laboratory for alternatives to animal testing (EURL ECVAM) and the Directorate General for Environment to carve out an EU-led replacement strategy. Measures must be imposed to avoid outsourcing, regulate commercial production, and ensure that antibody producers are fully supported. Trends: Millions of animals are used for the routine production of antibodies for research, monitoring, diagnostics, and therapeutics, although the true magnitude of use is unknown. The EU Directive on the protection of animals used for scientific purposes (2010/63/EU) requires that animals are not be used for scientific purposes where a non-animal alternative exists. Animal-friendly affinity reagents (AFAs) from non-immunised sources and produced by phage display are mature and available to replace animal immunisation methods for antibody production. In line with Directive 2010/63/EU, an EU-wide replacement programme must now take precedence. In this Opinion article, we outline recommended actions that must be prioritised.